Managerial Impediments and Quality of Leadership in Universities in Rivers State, Nigeria - Dawari Ekine; Robert-Okah (Zien Journals, 2021)
This study investigated the managerial impediments and quality of leadership in universities in Rivers State, Nigeria. The purpose of this study is to find out the managerial impediments and quality of leadership in universities in Rivers State, Nigeria. Descriptive design was adopted in carrying out the study. Five (5) research questions and hypotheses guided the study. The population of the study comprised the 2,674 university students in the Departments of Educational Management, and Business Education in Ignatius Ajuru University of Education and Rivers State University respectively. A sample size of 440 university students was drawn from the population of the study using the proportionate stratified random sampling techniques. A self-developed instrument titled “Managerial Impediments and Quality of Leadership Questionnaire (MIQLQ)” was used for data collection. The questionnaire was validated by experts in the field of Educational Management. Reliability co-efficient of 0.97 was obtained using Cronbach Alpha method of determining internal consistency of the instrument. Mean and standard deviation were used to answer five (5) research questions while the z-test was used to test five (5) null hypotheses at 0.05% level of significance. The result revealed that managerial impediments and quality of leadership can bring about infrastructural, financial, research, manpower/brain drain development and enhance adequate accreditation in higher education in Rivers State. It was concluded that managerial impediment and quality of leadership can bring about infrastructural, financial, quality research, manpower/brain drain development and adequate accreditation in higher education in Rivers State. It was therefore recommended among others that the government and leaders of higher institutions should incorporate the culture of infrastructural development and maintenance and there should be prudent management of finance for optimum institutional development.
Keywords: Managerial Impediments; Leadership; Institution; Universities